Sulfuration corrosion failure analysis of Inconel 600 alloy heater sleeve in high-temperature flue gas. (May 2022) - Wei, Chen; Wang, Zejun; Chen, Jianguo
Highlights: Sulfur can enter the matrix through Cr2 O3 oxide layer and diffuse along the grain boundaries. Corrosion products are mainly composed of γ austenite (matrix), Ni3 S2 and Cr2 O3 phases. Ni3 S2 is continuously generated and melted to promote the continuous corrosion. Abstract: The sulfuration corrosion behavior of Inconel 600 alloy in high-temperature flue gas was investigated. The element distribution around corrosion layer, corrosion morphology and the phase composition of the corrosion layer were analyzed by scanning electron microscope (SEM) and X-ray diffractometer (XRD), respectively. The results indicate that the alloy is susceptible to be corroded in high-temperature sulfur-containing atmosphere. The corrosion mechanism is that, on the one hand, sulfur (S) could penetrate the Cr2 O3 oxide layer, diffuse into the matrix along the grain boundary, combine with chromium (Cr) to form Cr sulfide and weaken the intergranular bonding strength. On the other hand, sulfur (S) in the flue gas and nickel (Ni) in the alloy matrix form Ni3 S2 with low melting point, which is continuously generated and melted during service, and eventually results in the constant occurrence of sulfuration corrosion.